The Impact of a Sustainable Progressive STEAM Program on Primary School Students’ Critical Thinking Dispositions and Mathematics Achievements - Küçük, Hasan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
This study, which was supported by a quantitative research paradigm with two experiments and two control groups of 4 × 4 quasi-experimental design, aimed to find out the impact of a sustainable progressive STEAM (SP-STEAM model) application model on 5th-grade primary school students’ critical thinking dispositions and mathematics achievements in North Cyprus. The treatment model was applied to two independent experimental groups for 14 weeks (first semester of 2021-2022 academic year). The split-plot multiple group analysis of variance (split-plot ANOVA) statistical techniques was used to calculate between- and within-group significances regarding exogenous variables. The SPSS-24 software package was used for the analysis. The Pre-test and post-test results deriving from the experiment and control groups revealed a significant effect of the SP-STEAM model upon the 5th-grade primary school students’ critical thinking dispositions, as measured using the CCTDI, mathematic achievements, as well as measured using a dedicated exam. The results of the analysis showed that the experiment groups where the SP-STEAM program was applied performed better across all sub-dimensions of the CCTDI, in comparison to the control groups where the progressive STEAM program was not applied. Cross-sectional splitplot ANOVA results yielded that the experiment group 1 and experiment group 2 displayed statistically significant differences F(3100) 40.581, p < 0.001 in comparison to control group 1 and control group 2, across pre-post test results, in terms of mathematics achievement. No significant difference was observed in favor of control groups. The results were discussed in detail in light of the related literature, with suggestions for further studies proposed.

ÖZ: Bu çalışma, 4×4 yarı deneysel tasarıma sahip iki deneme ve iki kontrol grubu ile gerçekleşmiş nicel araştırma paradigması tarafından desteklenmiştir. Kuzey Kıbrıs'taki ilkokul 5. Sınıf öğrencilerinin eleştirel düşünme eğilimleri ve matematik başarıları üzerinde sürdürülebilir bir ilerleyici STEAM (SP-STEAM modeli) uygulama modelinin etkisini belirlemeyi amaçlamıştır. Bu model, 14 hafta boyunca (2021-2022 Eğitim Yılı 1. Dönem) iki bağımsız deneme grubuna uygulanmıştır. Dışsal değişkenlere ilişkin olarak gruplar arası ve grup içi anlamlılıkları hesaplamak için split-plot çoklu grup varyans analizi (split-plot ANOVA) gibi istatistiksel teknikler kullanılmıştır. Analiz için SPSS-24 yazılım uygulaması kullanılmıştır. Deney ve kontrol gruplarından elde edilen ön test ve son test sonuçları, SP-STEAM modelinin 5. sınıf ilkokul öğrencilerinin eleştirel düşünme eğilimleri ve CCTDI kullanılarak özel bir sınav aracılığıyla ölçülen matematik başarıları üzerinde anlamlı bir etkisi olduğunu ortaya koymuştur. Analiz sonuçları, SP-STEAM programının uygulandığı deneme gruplarının, uygulanmayan kontrol gruplarına kıyasla CCTDI' nın tüm alt boyutlarında daha iyi performans gösterdiğini kanıtlamıştır. Kesitsel split-plot ANOVA sonuçları, deneme grubu 1 ve deneme grubu 2'nin matematik başarısı açısından ön-test ve sontest sonuçlarına göre kontrol grubu 1 ve kontrol grubu 2'ye karşı istatistiksel olarak önemli farklılıklar gösterdiğini (F (3100) 40.581, p< 0.001) ortaya koymuştur. Kontrol gruplarında anlamlı bir fark gözlemlenmemiştir. Sonuçlar, ilgili literatür ışığında detaylı bir şekilde tartışılmış ve ileriye dönük çalışmalar için öneriler sunulmuştur.
Doctor of Philosophy in Educational Sciences - Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Educational Sciences, 2024. Co-Supervisor: Assoc. Prof. Dr. Hamid Caner and Supervisor: Prof. Dr. Canan Zeki.
Keywords: Thesis Tez; Educational Sciences; Cognitive reading methods--Primary Schools--Primary education--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; STEAM Program--Primary School Students--Critical Thinking Dispositions--Mathematics Achievements; STEAM Education; CCTDI; 5th-grade Primary School Students; Critical Thinking Dispositions; Mathematics Achievements